Melanin deposition and key molecular features in Xenopus tropicalis oocytes - Hongyang Yi; Weizheng Liang; Sumei Yang; Han Liu; Jiayu Deng; Shuhong Han; Xiaohui Feng; Wenjie Cheng; Yonglong Chen; Jing Hang; Hongzhou Lu; Rensen Ran (BMC Biology, 2025)
Abstract Background Melanin pigmentation in oocytes is a critical feature for both the esthetic and developmental aspects of oocytes, influencing their polarity and overall development. Despite substantial knowledge of melanogenesis in melanocytes and retinal pigment epithelium cells, the molecular mechanisms underlying oocyte melanogenesis remain largely unknown. Results Here, we compare the oocytes of wild-type, tyr −/− and mitf −/− Xenopus tropicalis and found that mitf −/− oocytes exhibit normal melanin deposition at the animal pole, whereas tyr −/− oocytes show no melanin deposition at this site. Transmission electron microscopy confirmed that melanogenesis in mitf −/− oocytes proceeds normally, similar to wild-type oocytes. Transcriptomic analysis revealed that mitf −/− oocytes still express melanogenesis-related genes, enabling them to complete melanogenesis. Additionally, in Xenopus tropicalis oocytes, the expression of the MiT subfamily factor tfe3 is relatively high, while tfeb, mitf, and tfec levels are extremely low. The expression pattern of tfe3 is similar to that of tyr and other melanogenesis-related genes. Thus, melanogenesis in Xenopus tropicalis oocytes is independent of Mitf and may be regulated by other MiT subfamily factors such as Tfe3, which control the expression of genes like tyr, dct, and tyrp1. Furthermore, transcriptomic data revealed that changes in the expression of genes related to mitochondrial cloud formation represent the most significant molecular changes during oocyte development. Conclusions Overall, these findings suggest that further elucidation of Tyr-dependent and Mitf-independent mechanisms of melanin deposition at the animal pole will enhance our understanding of melanogenesis and Oogenesis.